Hugo and Russell's pharmaceutical microbiology - Gilmore, Brendan F.; Denyer, S. P.; Hugo, W. B. (William Barry). (Hoboken, NJ ; Chichester, West Sussex, UK : Wiley-Blackwell, 2023)
Pharmaceutical microbiology has a bearing on all aspects of pharmacy, from the manufacture and quality control of pharmaceutical products through to an understanding of the mode of action of antibiotics. Fully revised and restructured, drawing on the contributions of subject experts, and including material relevant to the European curricula in pharmacy, the eighth edition covers: biology of micro-organismspathogens and host responseprescribing therapeuticscontamination and infection controlpharmaceutical productioncurrent trends and new.
4.4.1 Polyene Antifungals -- 4.4.2 Azole Antifungals -- 4.4.3 Echinocandins -- 4.4.4 Synthetic Antifungal Agents -- 4.5 Medically Important Fungal Pathogens of Humans -- 4.5.1 Candida albicans -- 4.5.2 Aspergillus fumigatus -- 4.5.3 Histoplasma capsulatum -- 4.5.4 Cryptococcus neoformans -- 4.5.5 Dermatophytes -- 4.6 Emerging Fungal Pathogens -- 4.6.1 Saccharomyces cerevisiae -- 4.6.2 Non-albicans Candida Species -- 4.6.3 Penicillium marneffei -- 4.7 Antibiotic Production by Fungi -- Further Reading -- Chapter 5 Viruses and Other Acellular Infectious Agents: Characteristics and Control
Includes bibliographical references and index.
Description based upon online resource; title from PDF title page (viewed March 20th, 2023).
5.1 Introduction
WorldCat record variable field(s) change: 050, 650
Keywords: Pharmaceutical microbiology; Anti-infective agents; Pharmaceutical technology; Anti-Infective Agents; Technology, Pharmaceutical; Microbiological Phenomena; Microbiological Techniques; Pharmaceutical microbiology